DNA Repair–Related Gene Signature in Predicting Prognosis of Colorectal Cancer Patients - Lv, Min-Yi; Wang, Wei; Zhong, Min-Er; Cai, Du; Fan, Dejun; Li, Cheng-Hang; Kou, Wei-Bin; Huang, Ze-Ping; Duan, Xin; Hu, Chuling; Zhu, Qiqi; He, Xiaosheng; et al. (Frontiers in Genetics, 2022)
Background: Increasing evidence has depicted that DNA repair-related genes (DRGs) are associated with the prognosis of colorectal cancer (CRC) patients. Thus, the aim of this study was to evaluate the impact of DNA repair-related gene signature (DRGS) in predicting the prognosis of CRC patients. Method: In this study, we retrospectively analyzed the gene expression profiles from six CRC cohorts. A total of 1,768 CRC patients with complete prognostic information were divided into training cohort (n=566) and 2 validation cohorts (n=624 and 578, respectively). LASSO-Cox model was applied to construct a prediction model. To further validate the clinical significance of the model, we also validated the model with Genomics of Drug Sensitivity in Cancer (GDSC) and an advanced clear cell renal cell carcinoma (ccRCC) immunotherapy dataset. Results: Among 1,376 DRGs, a prognostic DRGS consisting of 11 distinct genes stratified patients into high and low -risk groups. In all cohorts, patients in the high -risk groups had significantly worse disease-free survival (DFS) compared with those in the low-risk groups (training cohort: hazard ratio (HR) = 2.40, 95% confidence interval (CI) = 1.67-3.44, P < 0.001; validation-1: HR = 2.20, 95% CI = 1.38-3.49, P < 0.001; validation-2 cohort: HR = 2.12, 95% CI = 1.40-3.21, P < 0.001). By validating the model with GDSC, we could see that among the chemotherapeutic drugs such as oxaliplatin, 5-fluorouracil and irinotecan, the IC50 of the cell line in the low-risk group was lower. By validating the model with ccRCC immunotherapy dataset, we can clearly see the overall survival (OS) of objective response rate (ORR) with complete response (CR) and partial response (PR) in low-risk group was best. Conclusions: DNA repair-related gene signature is a favorable prognostic model for patients with CRC, and our model can predict the response of cell lines to chemotherapeutic agents and potentially predict the response of patients to immunotherapy.